EE-RI-MAC: An energy-efficient receiver-initiated asynchronous duty cycle MAC protocol for dynamic traffic loads in wireless sensor networks - Yong, Yueh Tiam; Chow, Chee Onn; Kanesan, Jeevan; Ishii, Hiroshi (Academic Journals, 2011)
Introducing duty cycling in the MAC protocol used in wireless sensor networks has been proven to be an efficient way of prolonging the battery lifetime of the sensor nodes because idle listening is a high energy consumption factor. This concept has been proven efficient in the existing energy-efficient MAC protocols, including receiver-initiated MAC (RI-MAC). In this paper, we further enhance the RI-MAC protocol by introducing an asynchronous duty cycling method, in which the wakeup and sleep periods of a sender are alternating in order to reduce the wakeup period and so the energy efficient can be further improved. This method is called energy-efficient receiver-initiated asynchronous duty cycle MAC protocol (EE-RI-MAC). Specifically, the EE-RI-MAC protocol attempts to reduce the duty-cycle of a sender by adding sleep periods during ideal listening when the wakeup period is longer that certain value. From extensive simulation, it shows that the EE-RI-MAC achieves 17% higher energy efficiency that RI-MAC with the same throughput under a wide range of traffic loads, with a small increase in the delay period. © 2011 Academic Journals.